Asymmetric Lipid Vesicles: Techniques, Applications, and Future Perspectives as an Innovative Drug Delivery System - Denisse Gardea-Gutiérrez; Eduardo Núñez-García; Berenice E. Oseguera-Guerra; Manuel Román-Aguirre; Silvia L. Montes-Fonseca (MDPI AG, 2023)
Novel lipid-based nanosystems have been of interest in improving conventional drug release methods. Liposomes are the most studied nanostructures, consisting of lipid bilayers ideal for drug delivery, thanks to their resemblance to the cell plasma membrane. Asymmetric liposomes are vesicles with different lipids in their inner and outer layers; because of this, they can be configured to be compatible with the therapeutic drug while achieving biocompatibility and stability. Throughout this review, topics such as the applications, advantages, and synthesis techniques of asymmetric liposomes will be discussed. Further, an in silico analysis by computational tools will be examined as a helpful tool for designing and understanding asymmetric liposome mechanisms in pharmaceutical applications. The dual-engineered design of asymmetric liposomes makes them an ideal alternative for transdermal drug delivery because of the improved protection of pharmaceuticals without lowering adsorption rates and system biocompatibility.